The Ethical Dilemma of Green Economy: Examining the Human and Environmental Costs of Cobalt Mining in DRC (Global Journal of Human-Social Science, 2023)
This article discusses the ethical challenges of the green economy using cobalt mining in the DRC as an example The rising demand for cobalt a crucial mineral in the manufacture of renewable energy technologies has resulted in serious abuses of human rights and environmental damage in the DRC The article offers suggestions for addressing the ethical and environmental issues linked with cobalt mining in the DRC These ideas include responsible sourcing policy interaction with the community sustainable mining techniques and support for alternative technologies The production of essential minerals must prioritize human rights and environmental preservation and community engagement and sustainable mining techniques can assist in mitigating negative impacts and ensuring equitable distribution of benefits The shift to a low-carbon economy is crucial to combating climate change but it must be accomplished in an ethical and sustainable manner By addressing the ethical and environmental considerations involved with the creation of renewable energy technology we can ensure that the transition to a low-carbon economy is accomplished in a way that is beneficial to both people and the environment To build a more just and equitable green economy it is vital to take a complete and balanced strategy that evaluates the benefits and possible costs of renewable energy technologies
Keywords: ethical dilemma; green economy; cobalt mining; democratic republic of the congo (DRC); human rights violations